Optimization of low sulfur jerusalem artichoke juice for fossil fuels biodesulfurization process - Silva, Tiago (2013)
Most of the world’s energy is generated from the burning of fossil fuels such as oil and its derivatives. When burnt, these fuels release into the atmosphere volatile organic compounds, sulfur as sulfur dioxide (SO2) and the fine particulate matter of metal sulfates. These are pollutants which can be responsible for bronchial irritation, asthma attacks, cardio-pulmonary diseases and lung cancer mortality, and they also contribute for the occurrence of acid rains and the increase of the hole in the ozone layer. For these reasons countries around the world imposed legal maxima to sulfur concentration on fuels. Forcing companies to develop methods of removing the sulfur contained in the oil. The most common is hydrodesulfurization which employs high pressures and temperatures associated with complex metal catalysts making it extremely expensive. So, it becomes important to explore alternatives such as biodesulfurization (BDS). This process is based on the use of microorganisms for the removal of sulfur form even from the most recalcitrant compounds at atmospheric pressure and temperature, making it cheaper and more eco-friendly. However it still presents some drawbacks, such as being easily inhibited in the presence of sulfates, which have been shown to have great inhibitory effect even in amounts as low as 6 mg/l [1]. In order to further reduce the costs associated with BDS it is possible to explore alternative carbon sources, as previously shown with carob pulp syrup and recycled paper sludge [1, 2]. The main objective of this work is the optimization of sulfate removal, from Jerusalem artichoke juice, in order to use it as an alternative carbon source for BDS.